A review and synthesis of frameworks for engagement in health research to identify concepts of knowledge user engagement - Jull, Janet E; Davidson, Laurie; Dungan, Rachel; Nguyen, Tram; Woodward, Krista P; Graham, Ian D (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Engaging those who influence, administer and/or who are active users (“knowledge users”) of health care systems, as co-producers of health research, can help to ensure that research products will better address real world needs. Our aim was to identify and review frameworks of knowledge user engagement in health research in a systematic manner, and to describe the concepts comprising these frameworks. Methods An international team sharing a common interest in knowledge user engagement in health research used a consensus-building process to: 1) agree upon criteria to identify articles, 2) screen articles to identify existing frameworks, 3) extract, analyze data, and 4) synthesize and report the concepts of knowledge user engagement described in health research frameworks. We utilized the Patient Centered Outcomes Research Institute Engagement in Health Research Literature Explorer (PCORI Explorer) as a source of articles related to engagement in health research. The search includes articles from May 1995 to December 2017. Results We identified 54 articles about frameworks for knowledge user engagement in health research and report on 15 concepts. The average number of concepts reported in the 54 articles is n = 7, and ranges from n = 1 to n = 13 concepts. The most commonly reported concepts are: knowledge user - prepare, support (n = 44), relational process (n = 39), research agenda (n = 38). The least commonly reported concepts are: methodology (n = 8), methods (n = 10) and analysis (n = 18). In a comparison of articles that report how research was done (n = 26) versus how research should be done (n = 28), articles about how research was done report concepts more often and have a higher average number of concepts (n = 8 of 15) in comparison to articles about how research should be done (n = 6 of 15). The exception is the concept “evaluate” and that is more often reported in articles that describe how research should be done. Conclusions We propose that research teams 1) consider engagement with the 15 concepts as fluid, and 2) consider a form of partnered negotiation that takes place through all phases of research to identify and use concepts appropriate to their team needs. There is a need for further work to understand concepts for knowledge user engagement.